Association between transfer for surgery and mortality and disability among neonates in high income countries-A systematic review with meta-analysis. - Haribalakrishna Balasubramanian; Abhishek Srinivas; Prathamesh Khedkar; Anitha Ananthan; Diwakar Mohan; Nandkishore Kabra; Sanjay Patole (PLoS ONE)
Birthing in a hospital with on-site surgical facilities (co-located care) is considered preferable for neonates with surgical conditions. However, it may not always be feasible. Whether transfer of surgical neonates from birth hospital to a surgical facility affects the outcomes of this cohort is unclear. We conducted a systematic review to investigate the association of birth location/transfer with all-cause mortality and disability among neonates with congenital/acquired surgical conditions. Data Sources from PubMed, Embase, CINAHL, and Web of Science were searched till December 2024. Studies from high-income countries (HICs) comparing infants transferred to a surgical center for surgery versus infants born and operated in a co-located care facility were included. Random effects model was used for meta-analysis. The quality of studies and certainty of evidence were assessed using Newcastle-Ottawa Scale and the GRADE framework respectively. The primary outcomes of interest were all-cause mortality and neurodevelopmental impairment at latest follow up. A total of 61 studies from 20 HICs were included. Compared to co-located care, transfer for surgery did not increase the odds of risk-adjusted and crude mortality in neonates with congenital diaphragmatic hernia [adjusted odds ratio (aOR):0.86 (0.49 to 1.49), 5 studies, 8366 infants; crude OR:0.68 (0.51 to 0.91, i.e., decreased mortality), 22 studies, 12970 infants], critical congenital heart disease [aOR:0.79 (0.42 to 1.48), 3 studies, 13485 infants; OR:1.04 (0.66 to 1.64), 10 studies, 14447 infants], surgical necrotizing enterocolitis [aOR:0.99 (0.61 to 1.61), 4 studies, 5891 infants; OR:1.03 (0.64 to 1.65), 5 studies, 5915 infants], gastroschisis [aOR:1.07 (0.68 to 1.68), 2 studies, 5294 infants; OR:0.80 (0.48 to 1.35), 11 studies, 8708 infants], tracheo-oesophageal fistula [aOR:0.97 (0.39 to 2.39), 1 study, 937 infants; OR:0.62 (0.37 to 1.04), 4 studies, 4050 infants], congenital or perinatal intestinal conditions [OR:2.69 (0.26 to 28.34), 4 studies, 1799 infants]. Neurodevelopmental outcomes between the groups were comparable in the three studies that reported this outcome. Whilst many included studies were of good quality, certainty of evidence was very low due to their observational design and heterogeneity. In conclusion, transfer of neonates from the birth hospital to another facility for surgical intervention was not associated with increased risk of mortality or disability. The evidence from this comprehensive meta-analysis would be useful for clinicians, parents and health policy makers. Systematic review registration: PROSPERO CRD 42024565651.